Buddhist economics : - Payutto, P. A. (Buddhadhamma Foundation, 1998)
In this small volume, Venerable Dhammapitaka (P. A. Payutto) offers a Buddhist perspective on the subject of economics. While not seeking to present a comprehensive Buddhist economic theory, he provides many tools for reflection, ways of looking at economic questions based on a considered appreciation of the way things are, the way we are. I hope that making this work available in English may go at least a short way towards resolving what has been called the current 'impasse of economics,' and to awaken readers to the wide-reaching contemporary relevance of the timeless truths that the Buddha discovered and shared with us.